2016
DOI: 10.1111/jog.13012
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing intravenous leiomyomatosis after hysterectomy: Assessment of the need to perform complete resection

Abstract: Intravenous leiomyomatosis (IVL) is a rare smooth muscle tumor that may extend into extrauterine veins. A high IVL recurrence rate has been reported after hysterectomy. A 44-year-old woman underwent total hysterectomy as a result of uterine leiomyoma, and IVL within the left uterine vein was incidentally found during the surgery. A residual tumor within the right ovarian vein was detected on contrast-enhanced computed tomography (CT) two days postoperatively. The tumor was diagnosed as IVL because it showed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
7
1
Order By: Relevance
“…Of note, the intracardiac tumor in the present case was larger than the diameter of the inferior vena cava and, thus, was considered to have developed within the heart. This differs from the report by Maneyama et al [9] in which a spontaneous migration of a residual IVL to the heart, via the blood stream after hysterectomy, was described. The intracardiac tumor of the present case was adherent to the wall of the right atrium wall via a richly vascularized pedicle.…”
Section: Discussioncontrasting
confidence: 99%
“…Of note, the intracardiac tumor in the present case was larger than the diameter of the inferior vena cava and, thus, was considered to have developed within the heart. This differs from the report by Maneyama et al [9] in which a spontaneous migration of a residual IVL to the heart, via the blood stream after hysterectomy, was described. The intracardiac tumor of the present case was adherent to the wall of the right atrium wall via a richly vascularized pedicle.…”
Section: Discussioncontrasting
confidence: 99%
“…However, recent studies revealed that TH was sufficient, and bilateral oophorectomy was not associated with recurrence. 11,13,31 To determine the influence of different surgical types on recurrence, we analyzed our 166 regularly followed up patients. Fourteen eventually relapsed after a median follow-up of 36 months, and their detailed information is shown in Table S1.…”
Section: Discussionmentioning
confidence: 99%
“…The pelvic and venous masses in a typical IVL are continuous. Though its pathogenesis is unclear, possible theories include its origin from blood vessel wall (smooth muscle) or uterine fibroids invasion into the uterine vein with significant widespread ( 8 ). The IVL may grow along blood vessels, extending to the iliac vein, inferior vena cava, and even the heart ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though its pathogenesis is unclear, possible theories include its origin from blood vessel wall (smooth muscle) or uterine fibroids invasion into the uterine vein with significant widespread ( 8 ). The IVL may grow along blood vessels, extending to the iliac vein, inferior vena cava, and even the heart ( 8 ). There have been reports that IVL spontaneously migrates toward the heart through the bloodstream after hysterectomy.…”
Section: Discussionmentioning
confidence: 99%